A Little Good is Good Enough: Ethical Consumption, Cheap Excuses, and Moral Self-Licensing - Jannis Engel; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2017)
We explore the role of cheap excuses in product choice. If a product improves upon one ethically relevant dimension, agents may care less about other, completely independent ethical facets of the product. This `static moral self-licensing' would extend the logic of the well studied moral self-licensing over time. Our data document that static moral self-licensing exists. Furthermore, effects spill over to later, unrelated but ethically relevant contexts. Thus, static moral self-licensing and moral self-licensing over time amplify each other. Outsiders, though incentivized for correct estimates, are completely oblivious to effects of moral self-licensing, both, static and over time.
Keywords: D03; D84; 330; moral self-licensing; moral spillovers; cheap excuses; outsider beliefs; moral personality; homo moralis; preference module